Resposta de plantas de arroz em desenvolvimento inicial aos níveis de acidez e correção do solo em solo arenoso e argiloso do estado de Mato Grosso - Pires, Jeferson Vôlnei Alves (2021)
Rice (Oryza sativa L.) is one of the most consumed cereals in the world, being essential in the daily diet of the Brazilian population, providing part of the nutritional and caloric needs of human beings. The state of Mato Grosso is one of the most important agricultural areas in the country, where the predominance of soils in these regions is of the order of Oxisols with chemically poor characteristics, and soil correction is essential to provide conditions for plant development. The objective was to evaluate the response of upland rice cultivated in pots with two different types of soil as a function of acidity levels and lime levels. The experiment was carried out in a greenhouse at the Federal University of Mato Grosso (UFMT), Araguaia University Campus, Barra do Garças – MT. Two soils with different textures were used, one sandy (medium texture) and the other clayey (clay texture), which are representative of agricultural areas in the Cerrado. The experimental design used was completely randomized (DIC) in a 2x5 factorial scheme, with two soils (medium and clayey texture) and five doses of limestone (0.0; 0.5; 1.0 1.5; 2.0), with three replications, the soil was incubated with a mixture of two limestones for 30 days, one calcitic (34.98% CaO and 13.64% MgO) with 70.54% PRNT and the other dolomitic (37.8% % CaO and 13.2% MgO) with a PRNT of 67.67%, in the proportion 1:1. The variables analyzed were: number of tillers per plant, shoot dry weight, root dry weight and height. The results show that there was a significant effect for the shoot and root dry mass variables regarding the study of lime doses. The interaction between Soil types x Limestone doses significantly affected shoot dry mass. For the other variables there was no statistically significant effect. Under the conditions under which this study was carried out, we concluded that: shoot and root dry matter reduced according to the increase in lime doses in rice plants in early development; the doses of limestone and soil type did not influence the development of the number of tillers and plant height; It is necessary to study under these conditions in a longer period of cultivation, in order to know how the plant will express itself in its next stages of development.